(untitled) (Journal of Environmental Science and Natural Resources, 2013)
Field experiments were conducted to evaluate the effects of phosphatic biofertilizer with inorganic or organic sources of P on lentil (Lens culinaris Medikus) (var. Binamasur 2), Phosphatic biofertilizer (PB). All the fertilizers and cowdung were applied on the basis of soil test values and Integrated Plant Nutrient System (IPNS). Mixed cultures of two phosphate solubilizing bacteria were used as phosphatic biofertilizer (PB). PB was applied as liquid form with lentil seeds before sowing. Phosphatic biofertilizer with inorganic or organic sources of P influenced the growth and yield attributes and yields of lentil at both the locations. Phosphatic biofertilizer with 50% P from TSP gave the highest seed and stover yields as well as total P uptake by lentil compared to the 100% P from TSP. The results revealed that 50% inorganic or organic sources of P can be saved by the integrated using of phosphatic biofertilizer for the lentil cultivation in Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14819 J. Environ. Sci. & Natural Resources, 5(2): 225-230 2012